Autologous Costal Cartilage Graft—A New Method to Treat Articular Cartilage Defects: Case Report and Note of Surgical Technique - Gigante, Antonio; Cianforlini, Marco; Farinelli, Luca; Girotto, Riccardo; Aquili, Alberto (Joints, 2018)
Full-thickness articular cartilage defects do not heal spontaneously. Several techniques have been developed to address this issue, but none resulted in the restitutio ad integrum of the articular cartilage. The most frequent sites of chondral lesion in the knee are medial femoral condyle and patella. The patellofemoral lesions are characterized by outcomes that are generally worse than those of tibiofemoral ones. To date, it has been well recognized the chondrogenic potential of rib perichondrium, and costal cartilage grafts have been extensively used in reconstructive surgery. Considering the need to find a gold standard technique to restore articular defect, we developed and here described a new technique to repair cartilage lesions of the knee using autologous costal cartilage graft with its perichondrium. This innovative surgical approach can be used to treat full thickness articular defects using autologous hyaline cartilage, making it possible to cover wide defects. This one step technique is low invasive, not technically demanding with minimal donor site morbidity and it has low costs. The long-term clinical efficacy of the method remains to be evaluated.
Keywords: cartilage repair; patella; costal graft; rib perichondrium